2017
DOI: 10.1002/1878-0261.12132
|View full text |Cite
|
Sign up to set email alerts
|

RhoGDIβ promotes Sp1/MMP‐2 expression and bladder cancer invasion through perturbing miR‐200c‐targeted JNK2 protein translation

Abstract: Our most recent studies demonstrate that RhoGDIβ is able to promote human bladder cancer (BC) invasion and metastasis in an X‐link inhibitor of apoptosis protein‐dependent fashion accompanied by increased levels of matrix metalloproteinase (MMP)‐2 protein expression. We also found that RhoGDIβ and MMP‐2 protein expressions are consistently upregulated in both invasive BC tissues and cell lines. In the present study, we show that knockdown of RhoGDIβ inhibited MMP‐2 protein expression accompanied by a reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 66 publications
1
32
0
Order By: Relevance
“…3e). Previous studies have also reported that transcription factors, including AP-1 [30], Ets-1 [31], HSF1 [29], and Sp1 [32], are involved in initiating MMP-2 transcription in different experimental systems. The protein levels of HSF1,…”
Section: Mmp-2 Functioned As Mir-200a Downstream Effector For Promotimentioning
confidence: 89%
See 1 more Smart Citation
“…3e). Previous studies have also reported that transcription factors, including AP-1 [30], Ets-1 [31], HSF1 [29], and Sp1 [32], are involved in initiating MMP-2 transcription in different experimental systems. The protein levels of HSF1,…”
Section: Mmp-2 Functioned As Mir-200a Downstream Effector For Promotimentioning
confidence: 89%
“…Since our previous studies indicate that MMP-2 plays a key role in human BC invasion [26,29], the potential effect of miR-200a overexpression on MMP-2 expression was evaluated in both T24T and UMUC3. The results showed that miR-200a overexpression led to a profound upregulation of MMP-2 levels in both T24T and UMUC3 cells compared with their vector (Fig.…”
Section: Mmp-2 Functioned As Mir-200a Downstream Effector For Promotimentioning
confidence: 99%
“…For example, Pang et al reported that JNK2 acted as the target to mediate the miR-146a induced increase of cisplatin resistance in non-small cell lung cancer 24 . More importantly, in bladder cancer, JNK2 was also reported to be the target of miR-200c in the RhoGDIβ induced up-regulation of Sp1/MMP2 and promotion of bladder cancer invasion 25 .…”
Section: Discussionmentioning
confidence: 98%
“…Muscular invasive bladder cancer represents a major therapeutic challenge of this disease; therefore, understanding the mechanisms underlying invasion and progression are crucial to potential drug discovery against the invasive malignant disease. In the current studies, we explored XIAP could promote invasion and lung metastasis of human BCs through RhoGDIb/MMP-2 pathway [10,11], but the molecular mechanism of XIAP upregulation in human BC remains unclear. Our result showed that XIAP was overexpressed in human high-grade BCs, high metastatic human T24T cells, and in mouse invasive BCs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, XIAP can promote bladder epithelial cell malignant transformation through inhibition of p63α translation [9]. Our newly research reported that XIAP promotes bladder cancer metastasis through upregulating RhoGDIβ/MMP-2 pathway [10,11]. But the molecular mechanisms leading to this XIAP alteration during BC metastasis have not been explored.…”
Section: Introductionmentioning
confidence: 97%